Serum proteinogram of Chinese goose (Anser cygnoides) vaccinated or not against Newcastle disease - Paulillo, Antonio Carlos [UNESP]; Campioni, Josie Maria [UNESP]; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Santana, André Marcos [UNESP]; Fagliari, José Jurandir [UNESP]; Testi, Alan Jonathan Pereira [UNESP]; Denadai, Janine [UNESP] (My University, 2009)
The blood proteinogram was investigated in Chinese geese vaccinated or not against Newcastle disease, using Ulster 2C, B1 and LaSota strains. Total serum protein, globulins and albumin/globulin ratio showed no significant differences between birds vaccinated or not against Newcastle disease. Albumin concentration was significantly lower in 42 day-old Chinese geese vaccinated with LaSota strain. © Asian Network for Scientific Information, 2009.
Keywords: Albumin; Chinese goose; Lasota strain; Newcastle disease; Total serum protein; Anser; Anser cygnoides; Aves